The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.17240/aibuefd.2023..-1102529
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Jigsaw II Technique on Fourth Grade Students Knowledge Structures about the Concepts of Melting and Dissolution

Abstract: Araştırmanın amacı, öğrencilerin erime ve çözünme kavramlarına yönelik bilgi yapılarına Jigsaw II tekniğinin etkisini belirlemektir. Araştırma Marmara bölgesinde yer alan bir büyükşehrin bir ilçesinde 2021-2022 eğitim öğretim yılında dördüncü sınıfa devam eden 42 öğrencinin katılımı ile gerçekleştirilmiştir. Katılımcıların belirlenmesinde basit seçkisiz örnekleme yöntemi kullanılmıştır. Araştırma yarı deneysel yönteme göre tasarlanmıştır. Araştırma verileri bilgi yapısı testinin ön test ve son test olarak uygu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The research revealed that only 11% of the students had scientific knowledge. In their research conducted in primary school, Kandemir and Apaydın (2023) found that, as a result of the pre-test application, the scientific and consistent response score of the students towards the concepts of melting and dissolution was lower than the non-scientific response score.…”
mentioning
confidence: 96%
“…The research revealed that only 11% of the students had scientific knowledge. In their research conducted in primary school, Kandemir and Apaydın (2023) found that, as a result of the pre-test application, the scientific and consistent response score of the students towards the concepts of melting and dissolution was lower than the non-scientific response score.…”
mentioning
confidence: 96%